(untitled) (Homoeopathy for All, 2024)
Sleep is an opportunity for the brain and body to rest and be restored. In addition, many functions important to good health take place during sleep at night. In India, at least 10% of the people can’t sleep without the sleeping pills. Some sleep disorders are serious enough to interfere with normal physical, mental and emotional functioning. This article review about causes, risk factors, different type, clinical presentation general management including some home remedies management and homoeopathic way of treatment of sleep disorder and healthy sleep. Homoeopathy treats the person as a whole. It means that homoeopathic treatment focuses on the patient as a person, as well as his pathological condition.